Comparative Analysis Study of Different Positions by Hands and Feet on Functional Mobility Assessed by Five Times Sit to Stand Test on Post-Stroke Patients - Nini Natalia Li1, Bayu Santoso2, R. A. Meisy Andriana3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Five times sit to stand test (FTSTS) has been recognized for its validity and reliability in assessing muscle strength of the lower extremities functionally, evaluating functional mobility, balance and risk of falling in post-stroke individuals. However, there is no standard protocol for FTSTS implementation. Objectives: To analyze the differences in functional mobility assessed with FTSTS results in various poststroke post-stroke hand posture and posture changes. Method: There were 11 patients ischemic stroke patients enrolled in the study. The age ranked from 4060 years old. This study used an observational and cross-sectional study. The characteristic and FTSTS data was recorded in the Five times sit to stand test form that designed for this study. The data will then be analyzed using paired t-test in groups with SSPS 16.0 program. Results: The paired t-test results show that there are significant differences between the FTSTS results in both hand positions, either on the spontaneous feet position or asymmetric feet position (p = 0.038 and 0.020). There are no significant differences in FTSTS results with changes in spontaneous or asymmetric feet position (p = 0.779 and 0.278). Conclusion: The augmented hand position gives the best result to shift the center of the body mass on the post-stroke patient with post-hand changes. Then, there was no difference in functional mobility assessed by FTSTS in feet position changes of the post-stroke patient.